2020
DOI: 10.1108/ecam-08-2019-0448
|View full text |Cite
|
Sign up to set email alerts
|

Development of a tool for measuring building information modeling (BIM) user satisfaction – method selection, scale development and case study

Abstract: PurposeWith the increasing attention acquired from researchers and practitioners in Architecture, Engineering and Construction (AEC) industry, building information modeling (BIM) has fundamentally changed the approach we design, construct and delivery, as well as operate and maintenance of buildings and civil infrastructures. This study tries to provide an innovative perspective on BIM research. This study aims to analyze the necessity and feasibility of BIM user satisfaction research and define what BIM user … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…e results not only support the findings of Marefat et al [52] and Liu et al [35] but also supplement the above research. In addition, these results contradict research by scholars such as Qin et al [53], who say that the accuracy and functional advantages of BIM cannot improve the satisfaction of BIM users.…”
Section: Eoretical Significancesupporting
confidence: 90%
See 1 more Smart Citation
“…e results not only support the findings of Marefat et al [52] and Liu et al [35] but also supplement the above research. In addition, these results contradict research by scholars such as Qin et al [53], who say that the accuracy and functional advantages of BIM cannot improve the satisfaction of BIM users.…”
Section: Eoretical Significancesupporting
confidence: 90%
“…Advances in Civil Engineering produce different degrees of satisfaction in projects of different complexity [33][34][35]. For example, Hong et al [33] have adopted two sets of structural equation models and found that the difference in project complexity led to a change in the relationship between BIM execution quality and execution intention.…”
Section: Project Complexitymentioning
confidence: 99%
“…Website is a collection of web pages, which are usually summarized in a domain (address) or sub-domain [13]. This Domain or Subdomain is located on the World Wide Web (WWW) on the internet, Website (WWW) is a journey on the internet, such as email, instant messaging (IM), and voice over internet protocol (VolP) [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…He believes that no matter how reliable and valid the smart technologies are, it will not make sense if the AEC projects managers do not accept and adopt it. Liu et al [62] also believed user satisfaction is highly associated with the adoption and evaluation of new technologies. Hence, it is unavoidable to have site engineers and managers involved in the smart construction site implement process.…”
Section: Staff's Involvement Of Smart Construction Sitementioning
confidence: 99%